Handbook of Optical Fibers - Peng, Gang-Ding (Springer Nature Singapore : Imprint: Springer, 2019)
This handbook aims to be a comprehensive and up-to-date reference tool for students, scientists, engineers and industrial practitioners who are working in an area of the optical fiber field. The book includes five sections that cover the following subtopics as follows: • Optical Fiber Fundamentals including fiber materials and characteristics, fiber design, analysis, fabrication, test, etc; • Optical Fibers including all conventional and special fibers; • Optical Fiber Devices including all passive and active fiber devices and components, such as fiber couplers, fiber connectors, fiber gratings, fiber amplifiers and fiber lasers; • Optical Fiber Communication including main optical fiber communication techniques and systems • Optical Fiber Sensing including main optical fiber sensing and systems.